2011
DOI: 10.1007/s12031-011-9604-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Tau-Related Cognitive Defects in a Regulatable FTD Mouse Model

Abstract: The accumulation of proteins such as Tau is a hallmark of several neurodegenerative diseases, e.g., frontotemporal dementia (FTD). So far, many mouse models of tauopathies have been generated by the use of mutated or truncated human Tau isoforms in order to enhance the amyloidogenic character of Tau and to mimic pathological processes similar to those in FTD patients. Our inducible mice express the repeat domain of human Tau (Tau(RD)) carrying the FTDP-17 mutation ΔK280 in a "pro-aggregant" and an "anti-aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…Overexpression of both wild type and mutant Tau induces neurodegeneration in various animal models (14 -19); however, memory deficits and cell loss precede detectable NFT-like Tau pathology (20,21). Moreover, suppression of Tau expression improves memory function and halts further cell loss yet NFTs persist, suggesting that neurofibrillary pathology is not sufficient for neurodegeneration (22,23). Importantly, neurodegeneration occurs in some animal models overexpressing Tau despite the absence of overt neurofibrillary pathology (19,24).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Overexpression of both wild type and mutant Tau induces neurodegeneration in various animal models (14 -19); however, memory deficits and cell loss precede detectable NFT-like Tau pathology (20,21). Moreover, suppression of Tau expression improves memory function and halts further cell loss yet NFTs persist, suggesting that neurofibrillary pathology is not sufficient for neurodegeneration (22,23). Importantly, neurodegeneration occurs in some animal models overexpressing Tau despite the absence of overt neurofibrillary pathology (19,24).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…While the mechanisms by which FTDassociated mutations cause disease are still being determined, it is clear that they disrupt cell function in ways that can cause subtle structural and functional changes. [37][38][39][40][41][42][43] Mutationbased animal models of FTD have demonstrated subtle morphological changes in neurons, such as decreased synaptic density, altered spine morphology, and altered synaptic vesicle content, 40,41,44,45 as well as changes in physiological functions, such as excitatory postsynaptic potentials 41,44 and long-term potentiation. 45 These findings can be demonstrated in mice with behavioral abnormalities, such as anxiety and altered social interaction, months before neuropathological abnormalities develop.…”
Section: Discussionmentioning
confidence: 99%
“…41 In some cases, they are reversible. 45 Continued study of these types of changes may reveal markers that could be detected in humans using imaging, gene expression, protein quantification, or other biological variables. Beyond FTD, this phenomenon may extend to other genetic neurological disorders, including Huntington's disease and spinocerebellar ataxias, where cases of psychiatric illness preceding motor symptoms have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that LTD was readily inducible across mossy fiber (mf-LTD) synapses in tau knockout mice (Decker and others, 2015), raising the interesting question as to how to explain these opposing results. The answer likely stems from features of the different experimental models in terms of the age of the hippocampal slices and the induction protocols used for plasticity (Kemp and others, 2000;Ahmed and others, 2011), and/or reflects a specialisation of tau function at specific hippocampal synapse circuits depending on the locus or mechanisms of synaptic plasticity (e.g., tau-independent mf-LTD is expressed pre-synaptically (Kobayashi and others, 1996) whereas tau-dependent LTD at CA3-CA1 synapses is generally regarded as post-synaptic (Collingridge and others, 2010)). Therefore, it is undoubtedly important to probe further into a possible age-dependent and synapse-specific involvement of tau in mechanisms of synaptic plasticity induction, which could also provide further understanding into why certain forms of tau lead to neurotoxicity in the matured and/or aged brain.…”
Section: Tau Regulation Of Synaptic Functionmentioning
confidence: 99%